The evolving maritime balance of power in the Asia-Pacific maritime doctrines and nuclear weapons at sea - Prabhakar, Lawrence W.; Ho, Joshua; Bateman, W. S. G. (Walter Samuel Grono) (Institute of Defence and Strategic Studies, 2006)
The Asia-Pacific region has emerged as the hub of global geo-political, geo-economic and geo-strategic significance in the post-Cold War period. This volume examines the national maritime doctrines and the nuclear weapons developments at sea of the four major powers in the Asia-Pacific.